The Relationship between Health Literacy and Online Health Information Search among Caregivers of Pediatric Oncology Children - SU Jun, WANG Jiamin, SUN Xiaojie (Zhongguo quanke yixue)
Background Cancer is the second leading cause of death among children. The level of health literacy of caregivers of pediatric oncology patients not only affects their ability to search for health information on the Internet, but also has an impact on the health outcomes of patients. There is a lack of study exploring the relationship between health literacy and online health information search among caregivers of pediatric oncology patients. Objective To explore the relationship between health literacy and online health information search among caregivers of pediatric oncology patients and to analyze the factors that influence caregivers' online health information search. Methods A total of 424 caregivers of pediatric oncology patients were included in the study using purposive sampling in three hospitals in Shandong Province from May to August 2021, as well as whole cluster sampling and snowball sampling in Guangdong Province through Shenzhen HengHui Public Welfare Foundation from June to August 2022 as subjects. The survey was conducted using the basic characteristics questionnaire and the health literacy questionnaire, and subjective answers from caregivers were used to confirm whether online health information searches were done. Point two-column correlation analysis was used to test the correlation between health literacy and online health information search among caregivers of pediatric oncology patients; binary Logistic regression (forward stepwise regression based on maximum likelihood estimation) was used to analyze the influencing factors of online health information search among caregivers of pediatric oncology patients. Results The health literacy scores of caregivers of pediatric oncology patients were (2.60±0.30) (2.76±0.30) (2.76±0.30), and (2.76±0.30) for the four dimensions of "Perceived understanding and support from healthcare professionals""Evaluation of health information""Ability to interact with healthcare professionals", and "Know enough about health information to know what to do", respectively; the proportion of high health literacy was 56.13%, 63.21%, and 63.21%, 35.61%, respectively; negative correlation (r=-0.161), positive correlation (r=0.006), positive correlation (r=0.073), positive correlation (r=0.102), with online health information search, respectively. The education level of junior high school, high school/vocational school, or college/junior college and above, one-child family, "evaluation of health information" and "ability to interact with healthcare professionals" were facilitating factors for caregivers to conduct online health information search; and "perceived understanding and support from healthcare professionals" was a hindering factor for caregivers to conduct online health information search. Conclusion Most caregivers of pediatric oncology patients search for health information on the Internet, and a higher level of education, being a one-child family, having a better ability to assess health information, maintaining positive interactions with healthcare professionals, and rarely feeling the understanding and support of healthcare professionals can promote the occurrence of online health information searching behaviors among caregivers of pediatric oncology patients. The government and related departments should actively carry out health education initiatives for caregivers of pediatric oncology patients to improve their health literacy and ability to use the Internet to search for health information.